A novel approach in the synthesis of CdS/titania nanotubes array nanocomposites to obtain better photocatalyst performance - Pratiwi, Reno; Ibadurrohman, Muhammad; Listiani Dewi, Eniya; -, Slamet (Communications in Science and Technology, 2023)
Studies that seek to improve the performance of photocatalyst continue to develop. Several observations have been made on the effect of using ultrasonic waves during the synthesis process of CdS/Titania Nanotubes Array (CdS/TiNTA) nanocomposites on an ability to degrade ciprofloxacin solution (CIP) and produce hydrogen. Therefore, the nanocomposite synthesis process uses the Successive Ionic Layer Adsorption and Reaction (SILAR) method, with (CH3COO)2Cd and Na2S as the precursors. During the SILAR process, sonication was applied for 60 minutes and carried out in the amorphous phase of TiO2 to increase the effectiveness of contact between the two semiconductors. The synthesis results were confirmed in term of their crystallinity, morphology, the presence of components on the surface, and the shift of bandgap by means of XRD, FESEM, FTIR, and UV-Vis DRS characterization, respectively. Photocatalytic activities of the nanocomposites were evaluated in a system containing 10 ppm CIP solution, on the purpose of observing their ability to degrade CIP and produce hydrogen. Our findings revealed an improvement in crystallinity, successful semiconductor coupling, and a band gap narrowing in the synthesized nanocomposites. Furthermore, the photocatalysts synthesized in the amorphous TiO2 and by sonication during SILAR offered doubled production capacity of hydrogen (0.191 mmol/m2) as compared to photocatalysts synthesized without sonication (0.092 mmol/m2). Compared to similar photocatalysts synthesized using the SILAR method in the crystalline phase, photocatalysts synthesized in the amorphous phase exhibited four-fold higher hydrogen production (0.044 to 0.191 mmol/m2). This prominent ability of the nanocomposites is related to the success of CdS adhering well to TiO2 surface to form nanocomposites, so that the bandgap energy position of CdS that is strong in the reduction reaction greatly contributes to improve the performance of the resulting photocatalyst, which is very advantageous in terms of its ability in water-splitting reactions.